Mesoporous molecular sieves containing niobium(V) as catalysts for the epoxidation of fatty acid methyl esters and rapeseed oil. (10th November 2017) - Dworakowska, Sylwia; Tiozzo, Cristina; Niemczyk-Wrzeszcz, Marta; Michorczyk, Piotr; Ravasio, Nicoletta; Psaro, Rinaldo; Bogdał, Dariusz; Guidotti, Matteo
Abstract: Niobium-containing mesoporous silica (Nb–SiO2 ) catalysts, which showed previously promising performances in the liquid-phase epoxidation of alkenes, were here applied to the epoxidation of unsaturated fatty acid methyl esters (FAMEs), selectively hydrogenated FAMEs and rapeseed oil triglyceride with aqueous hydrogen peroxide. Niobium-silica solids were prepared via grafting of niobocene dichloride onto the surface of different porous silica-based supports (non-ordered SiO2, ordered mesoporous MCM-41 and SBA-15 molecular sieves) via a dry impregnation procedure. Promising performance with very good selectivity towards desired monoepoxides were obtained, in particular over a Nb-grafted silica catalyst prepared from a commercial non-ordered silica support. Graphical abstract: Image 1 Highlights: Mesoporous Nb-SiO2 catalysts were efficiently used in epoxidation of oil derivatives. Aqueous hydrogen peroxide was used as an oxidant in moderate excess. The epoxidation of partially hydrogenated FAMEs maximised the formation of epoxides. Promising yield and selectivity values towards monoepoxidised FAMEs were achieved.